Assessment of surface-engineered hyaluronic acid-nano-zeolitic imidazolate framework in the embryo zebrafish model - Nor Afifah, Mohd Nordin (2024)
Colon cancer is potentially life-threatening if not detected early. Colon cancer is treatable, typically through surgery which often combines with chemotherapy or radiation therapy yet has many limitations. Hence, to address the limitations of chemotherapy medications, it is significantly crucial for the development of targeted nanosystems that can be highly selective towards cancer cells while enhancing the efficacy and safety of the drug delivery system. In previous research, a zeolitic imidazole framework-8 (ZIF-8), An emerging nanoparticle was suppressed to surface engineered using Hyaluronic Acid (HA) acting as targeting agent for these studies through one-pot solvothermal reaction. The unique characteristics of pristine nano zeolitic imidazole framework-8 (nZIF-8) and Hyaluronic Acid-engineered nano zeolitic imidazole framework-8 (HA@nZIF-8) were assess and execute in of surface area, particle size, newly formed functional groups and surface structure. When modified with the hyaluronic acid, the nano zeolitic imidazole framework-8 likelihood to improve the optimal chemotherapeutic dosage for colon cancer while minimizing unnecessary toxicity towards healthy cell and facilitate higher selective targeting system.